The Interpersonal Meaning of English Posts Written by Aceh Bloggers on Steemit - Jumaida Fajar Nasriati; Zulfadli A. Aziz; Siti Sarah Fitriani (English Education Journal, 2019)
This research was conducted to analyze the interpersonal meaning of English posts published by Acehnese bloggers on social media-based blog, Steemit through the systemic functional linguistic analysis by Halliday (1985). Steemit is a blog community which has a function as social media. There were twenty posts that were sorted to be analyzed in this research. In sorting the posts, the researchers classified the posts that used topics or tags “Aceh”, “History”, “Writing”, “Tourism”, Education, “Writing”, “Nature”, “Life” and “Photography”. In analyzing the posts, there are three issues that have been the focus of the research; exchange of interaction type, mood type and attitude appraisal that are realized in the posts. There were two kinds of exchange of interaction, the exchange of giving information or good and service and demanding information or good and service. From this research, giving information was the most dominant exchange of interaction and there was a small number of demanding information found. Meanwhile, none of the interactions in terms of giving or demanding goods and service as the interaction exchange were found. Another focus is mood element structures of the clauses in the posts. Giving information was the highest number found which revealed that declarative was the most dominant mood type realized in the posts. In the posts, however, it was found that there was a small number of appraisal value. Overall, the three appraisal values were all presented in the whole posts. They were judgement, affect and appreciation. However, the three values also showed very small number.